The Music of Silence - Bocelli, Andrea (London Virgin, 2000)
This is Bocelli's true story, told in his own words for the first time. He talks frankly about his blindness, the importance of his family, his stage fright and the pressures of international stardom.
Include Illustration
Keywords: Tenors (Singers) -- Italy -- Bocelli, Andrea